(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is motivated to investigate the impact of foreign direct investment (FDI) on the economy of Malaysia and Thailand for the past 28 years with a specific focus on examining the strength of relationship between net FDI and three key economic indicators – real Gross Domestic Product (GDP), exchange rates and long-term interest rates. Within the framework of Keynesian Income Theory, this paper deploys both Ordinary Least Squares (OLS) regression and Engle-Granger Cointegration test as estimation tools to model the yearly secondary data from 1992 through 2019. The empirical findings show that net FDI does have some influence on real GDP, exchange rates and long-term interest rates in these two countries. From Pearson correlation coefficient, we observe a strong positive correlation between net FDI and real GDP. It is clear that net positive FDI plays an important role not only in sustaining GDP growth but also in strengthening host country’s exchange rates. Both Malaysia and Thailand must look into devising good trade and investment policies which could attract quality FDI that optimizes scarce national resources in the best possible manner.